Conquer Cancer bridging children with leukemia and the public of their pain experience through an empathic landscape design - Ysaac, Sofia Francesca C. (College of Architecture, University of the Philippines Diliman, 2018)
Pain is a universal, complex process, and constant part of the human experience as it plays an important role in our lives. For children diagnosed with leukemia, they experience pain from the disease itself, as well as from its treatment modalities. At a very young age, such children have a limited capacity in expressing the pain they feel. Graphic communication, such as making drawings and sketches, is one of the methods in which these children are able to share their pain experience. Interview methods for the general physician and the childhood leukemia survivor were included for additional information to the study. Ultimately, these drawings may offer a means of understanding what it means to be like a child living with leukemia. This study aims to understand the process of pain in leukemia, specifically Acute Lymphoblastic Leukemia (ALL), to promote empathy to the general public about the pain experience of children with leukemia, to produce and translate related activities and experiences to the landscape, and to relieve from their pain. An empathic landscape approach was incorporated to help identify with the pain of children with leukemia, as the public will then be able place themselves in the shoes of these children. Keywords: pain, leukemia, children, public, empathy, landscape